Non-Nucleotide RNA-Dependent RNA Polymerase Inhibitor That Blocks SARS-CoV-2 Replication - Dejmek, Milan; Konkoľová, Eva; Eyer, Luděk; Straková, Petra; Svoboda, Pavel; Šála, Michal; Krejčová, Kateřina; Růžek, Daniel; Boura, Evzen; Nencka, Radim (Viruses, 2021)
SARS-CoV-2 has caused an extensive pandemic of COVID-19 all around the world. Key viral enzymes are suitable molecular targets for the development of new antivirals against SARS-CoV-2 which could represent potential treatments of the corresponding disease. With respect to its essential role in the replication of viral RNA, RNA-dependent RNA polymerase (RdRp) is one of the prime targets. HeE1-2Tyr and related derivatives were originally discovered as inhibitors of the RdRp of flaviviruses. Here, we present that these pyridobenzothiazole derivatives also significantly inhibit SARS-CoV-2 RdRp, as demonstrated using both polymerase- and cell-based antiviral assays.
Keywords: RNA-dependent RNA polymerase; Cell Line; Dose-Response Relationship, Drug; adenosinmonofosfát; alanin; vztah mezi dávkou a účinkem léčiva; Coronavirus RNA-Dependent RNA Polymerase; Enzyme Inhibitors; SARS-CoV-2; antivirové látky; COVID-19; non-nucleotide inhibitor; koronavirová RNA-replikasa; Microbial Sensitivity Tests; Adenosine Monophosphate; Benzothiazoles; replikace viru; Pyridones; zvířata; Humans; SAR-CoV-2; pyridony; viabilita buněk; Cell Survival; buněčné linie; mikrobiální testy citlivosti; Antiviral Agents; antiviral agents; Virus Replication; Alanine; lidé; benzothiazoly; inhibitory enzymů; Animals